Evaluating the Success of E-Invoice Implementation at a State-Owned Enterprise Using DeLone & McLean IS Success Model - Amalina, Debbie; Suryani, Erma (IPTEK Journal of Proceedings Series, 2020)
E-Invoice considered as one of the most implemented financial information systems these recent years. E-Invoice had grown from a system that brings convenience, into a part of the strategy to fulfill corporate expectation. However, it’s uncertain whether E-Invoice implementation indeed successfully brings proven benefits into the company business. Therefore, the aim of this study is to identify the indicators that affect the success of E-Invoice implementation in a particular state-owned company, based upon DeLone & McLean IS Success Model. In terms of evaluation, previous research regarding E-Invoice mostly discussed about the key factors that influence the adoption of E-Invoice. Lesser literatures purposed at studying the success of the implementation, related to the system performance. According to DeLone & McLean IS Success Model, there are six variables used as basic measurement, namely information quality, system quality, service quality, user satisfaction, intention to use, and net benefits. Following that, a set of structured questionnaire arranged and distributed to 34 users of an E-Invoice system provided by a state-owned enterprise headquartered in Rembang, Indonesia, including vendors and employees. The data then will be processed using Partial Least Square (PLS) method. The result showed that Information Quality and System Quality gave significant impact to User Satisfaction and User Satisfaction gave significant impact to Net Benefits. Meanwhile, Service Quality is not proven empirically to gave significant impact to both User Satisfaction and Intention to Use.